Semiconductor whiskers for humidity sensors - Ostrovskii, I. P.; Druzhinin, A. O. (Physics and Chemistry of Solid State, 2020)
In present paper p-type GaPAs whiskers doped with Cu were obtained by VLS method in close bromine system. The whiskers have various morphologies and geometries: imperfect needle-like crystals, ribbons, perfect needle-like crystals and thin plates. The whiskers of various morphologies serve as thermoresistores with TCR of about 1-2 %. The whisker I-U characteristics were investigated dependent on their geometry and external conditions (humidity). Voltage arising on the thermoresisor for two polarities of current passing through it was shown to be dependent on air humidity. Miniature semiconductor sensors of humidity based on GaPAs whiskers have been designed. Physical principles of operation, the perculiarities of design, and main performances of the microsensors were discussed. The whiskers of small diameter (d=50 μm) were shown to measure humidity in the range j=35...97% with sensitivity to humidity g =DU/Uj »2.5×10-3. The miniature dimensions of the whiskers provides very rapid response (of about a few sec) and small time of recovery (less than 30 sec).